Memahami Hadis dalam Perspektif Sains Modern: Kajian Teori dan Metode - Aulia Rahmanini; Syaza El-Millah Matondang; Achyar Zein (Substantia: Jurnal Ilmu-Ilmu Ushuluddin)
In the era of modern scientific advancements, there is an increasing need to reassess the methods of hadith interpretation to ensure its relevance to contemporary scientific developments. Many hadiths explicitly address scientific phenomena, but their proper interpretation requires careful and methodological approaches. This study aims to analyze the theories and methods used in interpreting hadiths, particularly in the context of modern science, and to explore how the values embedded in hadiths can contribute to the advancement of science and technology. The study employs a qualitative approach using library research methods. Primary data consists of hadiths sourced from authentic hadith collections, while secondary data is derived from relevant scientific literature. The analysis is conducted through content analysis and comparative methods, comparing hadiths with contemporary scientific findings. The results showed that many hadiths align with scientific phenomena, such as those concerning embryonic development, food consumption, and the benefits of Zamzam water, which correspond to modern scientific discoveries. Understanding hadiths within the framework of science requires the application of appropriate theories and methods, such as thematic and linguistic analysis. This study reaffirms that integrating hadith and modern science is crucial to ensuring the relevance of Islamic teachings in contemporary contexts. The use of proper interpretative methods can lead to accurate and meaningful interpretations, enriching the dialogue between religion and science.